Phenotypic Stability of some Promising Strains of Cenchrus ciliaris Linn. In Arid and Semi-arid Regions of Rajasthan - Bhati, G. N.; Sharma, S. K.; Harsh, L. N. (Indian Forester, 1985)
Eight promising strains of Cenchrus ciliaria were studied at three different locations i.e. Jodhpur, Pall and Samdari for three consecutive years from 1978 to 1980, for their stability. Although Strains No. 1263 showed average stability in all environments, but high deviations mean square values suggest strengthening of breeding efforts to develop strains with high stability and general adaptability for arid and semi-arid regions of Rajasthan desert.